CREATING STRATEGIC COST KNOWLEDGE FOR MANAGEMENT AND PRODUCT PRICING DECISIONS: Case Company X - Lähdemäki, Vesa (My University, 2011)
Operational cost accounting has always been an important subject in management. The topic has however been neglected in the case company in some aspects. The actual basic costs behind the manufactured products are not in reality known. This causes pricing with information that can not be in reality trusted and the managing of the company is made difficult. This study’s main objective is to provide strategic cost information for pricing and management purposes. The foundation for more exact upcoming unit cost calculations is also provided. The information attained with this study is aimed primarily on helping the case company in times of change. The objectives of the study are reached with first presenting operational cost accounting and pricing theory, and then applying the theory to the case company’s characteristics. This results in forming cost structures, cost centres, cost categories, calculating cost estimations, and then finally to calculating machine centre operating costs. The manufacturing processes, the personnel, and the costs needed to be understood before any planning could be done. In gathering the needed information both quantative and qualitative methods were used. After getting familiarized with the situation and the environment meetings, financial reports, and bookkeeping information were used for attaining and forming the needed information. The main empirical research results were finding out the proportions of the different costs on the case company’s cost structure and attaining the machine centre specific operating costs with different machine utilizations. The study was problematic at times because it was made in addition to the theory partly on the opinions of the case company’s personnel. For some a topic could be a problem, as for the others a potential benefit. The results of the study show the importance of understanding the company-specific situation when configuring operational cost calculations and cost structures.
Keywords: Operational cost accounting; pricing; product cost structure; operating costs; fi=Tuotantotalous|en=Industrial Management|